2017
DOI: 10.3390/rs9121277
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Coupled Vegetation Phenology and Productivity are Biome-Specific in the Northern Hemisphere

Abstract: Global warming has greatly stimulated vegetation growth through both extending the growing season and promoting photosynthesis in the Northern Hemisphere (NH). Analyzing the combined dynamics of such trends can potentially improve our current understanding on changes in vegetation functioning and the complex relationship between anthropogenic and climatic drivers. This study aims to analyze the relationships (long-term trends and correlations) of length of vegetation growing season (LOS) and vegetation product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 77 publications
1
7
0
1
Order By: Relevance
“…Jeong et al [17] found that the SOS advanced by 5.2 days during the early period of 1982-1999 in the NH, but this magnitude reduced to only 0.2 days in the later period of 2000-2008. Meanwhile, Wang and Fensholt [18] reported that changes in the SOS were biome-specific in the NH (>30 • N) during 1982-2013, indicating complex relationships and interactions that are induced by ongoing climate change and increasingly intensive human disturbances. At the regional scale, SOS anomalies in high latitudes, including the Arctic and boreal ecosystems [19][20][21] and Europe [22][23][24], and middle latitudes, including eastern China [25] and the Tibetan Plateau [26][27][28], have been explored separately.…”
Section: Introductionmentioning
confidence: 99%
“…Jeong et al [17] found that the SOS advanced by 5.2 days during the early period of 1982-1999 in the NH, but this magnitude reduced to only 0.2 days in the later period of 2000-2008. Meanwhile, Wang and Fensholt [18] reported that changes in the SOS were biome-specific in the NH (>30 • N) during 1982-2013, indicating complex relationships and interactions that are induced by ongoing climate change and increasingly intensive human disturbances. At the regional scale, SOS anomalies in high latitudes, including the Arctic and boreal ecosystems [19][20][21] and Europe [22][23][24], and middle latitudes, including eastern China [25] and the Tibetan Plateau [26][27][28], have been explored separately.…”
Section: Introductionmentioning
confidence: 99%
“…Concepts like biomes (developed throughout this review and defined under Final remarks), ecozones, and formations have described such distributions at the regional and global scale due to the importance of this global scale for conservation biology (Chytrý et al 2020) and answering basic ecological questions (Mucina 2019). For example, the biome concept has been used to examine diversity-productivity (Madrigal-González et al 2020) and species-area (e.g., see Dengler et al 2020) relationships, quantify temporal dynamics (Wang and Fensholt 2017), model historical distributions and shifts following climate change (Rowland et al 2016),…”
Section: Introductionmentioning
confidence: 99%
“…Jeong et al (2011 concluded that the SOS advanced by 5.2 d in the early period (1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999) but advanced by only 0.2 d in the later period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) over the NH. Wang and Fensholt (2017) reported that temporal changes in coupled vegetation phenology and productivity are biome-specific in the NH, which indicates complex relationships and interactions between vegetation phenology and productivity. At regional scales, vegetation phenology changes in Fennoscandia (Menzel and Fabian 1999, Bogaert et al 2002, Fu et al 2014 have been separately studied.…”
Section: Introductionmentioning
confidence: 99%